The sociological imagination - Mills, C. Wright; Gitlin, Todd (Oxford Oxford University Press, 2000)
C. Wright Mills is best remembered for his highly acclaimed work The Sociological Imagination, in which he set forth his views on how social science should be pursued. Hailed upon publication as a cogent and hard-hitting critique, The Sociological Imagination took issue with the ascendant schools of sociology in the United States, calling for a humanist sociology connecting the social, personal, and historical dimensions of our lives.